On Target : - Rowley, Laura (J. Wiley, 2003)
The first behind-the-scenes look at the stunning success of America's hippest discount retailer. Founded in 1962 by Minnesota-based department store Dayton's, Target has grown to become America's second most profitable retailer behind Wal-Mart. On Target is the first in-depth look at the business leaders and strategies that made Target such a runaway success. The company's easily recognizable red-and-white logo, youthful television advertisements, and upscale partnerships-with designers like Michael Graves, Mossimo, and Todd Oldham-have not only removed the stigma traditionally attached to discount store shopping, but actually made it hip to be frugal. In the process, the company has cemented its place as the favorite discount retailer of middle- and upper-income families across the country. In On Target, award-winning business journalist Laura Rowley examines the methods and the success of the company from its shrewd merchandising strategy to its clever marketing campaigns, ingenious branding effort, and extensive philanthropy . An excellent education in how to beat the competition even in a crowded and weak retail market, Target's story details the history and incredible success of a unique company and an enticing, unmistakable brand. Both insightful and entertaining, On Target offers important business lessons for executives and managers in need of a bull's-eye.